GENDERED RESISTANCE AND EMOTIONAL SURVIVAL IN FAIR PLAY (2023) AND MARIE CURIE (2019) - Ernawati, Asih; Riyatno, Riyatno; Wahyuningsih, Titik (BASIS (Bahasa dan Sastra Inggris), 2025)
This study examines how gendered power struggles are represented through the female protagonists of Fair Play (2023) and Radioactive (2019). Both narratives center on Emily and Marie Curie who navigate male-dominated professional environments shaped by patriarchal norms and institutional hierarchies. The purpose of this comparative study is to deepen feminist readings of contemporary and historical female figures while fostering critically empathetic engagement with visual narratives. The research utilizes a comparative critical analysis framework, drawing on the theories of Judith Butler, Michelle M. Lazar, and bell hooks to explore how institutionalized misogyny, emotional labor, and resistance are constructed on screen. The findings reveal that both protagonists experience layered forms of marginalization, including workplace bias, emotional burden, and social surveillance. Yet, each asserts agency, Emily through reclaiming her dignity in the corporate world, and Marie Curie through intellectual defiance in academia. This study contributes to feminist film criticism by highlighting the emotional cost of women’s survival within gendered structures and underscoring the need for more intersectional and humanized portrayals of female agency in media.